GROSS PATHOLOGICAL FINDINGS OF AFRICAN SWINE FEVER SUSPECTS IN OEBELO, KUPANG REGENCY, 2021 - Sanam, Maxs U. E.; Gelolodo, Maria Aega; Toha, Larry R. W.; Utami, Tri; Simarmata, Yohanes T. R. M. R.; Murni, Theresia F. I. M. D. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
African swine fever (ASF) is a destructive re-emerging swine disease that has posed a serious economic threat to the global pig farming sector. In past years, ASF has rapidly spread over Europe, Asia, and Oceania, and begin to enter Indonesia in the middle of 2019. The clinical and pathological symptoms of ASF are influenced by the strain's virulence, the transmission pathway, and the pig's immunological and health status. ASF’s clinical manifestations are known to evolve, from after an invasion enters a new free region to after the disease has been established in the territory for a longer period. Identifying ASF clinical signs and pathological changes is crucial for a comprehensive and reliable early detection system. The objective of this research is to observe and identify gross pathology in ASF suspect pigs in order to obtain a better understanding of the cause of death. Two dead pigs from a farm in Oebelo village, Kupang regency, Indonesia with a recent history of massive deaths had been examined in this study. The post-mortem results showed that hemorrhagic splenomegaly and hemorrhagic lymphadenitis were the main lesions observed at the examinations. Furthermore, hemorrhages were also found in various internal organs such as the kidneys, liver, and heart. To determine the exact cause of the pigs' deaths, a molecular diagnostic test should be conducted.